The Fifth Decade of Cardiac Pacing. - Barold, S. Serge (John Wiley & Sons, 2007)
There have been major advances in the field of cardiac pacing over the last decade. Celebrating five decades of this technology, the contributors to this volume emphasize new techniques for the treatment of congestive heart failure.